A Preliminary Study of College Students’ Levels of Humility and Disability Attitudes - Worachek, Kelsey; Leibham, Mary Beth (My University, 2018)
The purpose of this study was to explore college students' levels of dispositional and intellectual humility and the potential link between humility and disability attitudes. We predicted that those with higher levels of dispositional humility would have more positive disability attitudes. We believe this study is important for understanding various factors related to college students’ disability attitudes, particularly if humility is related to disability attitudes.
Color poster with text and charts.
Keywords: Disability attitudes; Humility; College students; Posters